1996
DOI: 10.1164/ajrccm.153.5.8630597
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic mucus hypersecretion with FEV1 decline and chronic obstructive pulmonary disease morbidity. Copenhagen City Heart Study Group.

Abstract: The aim of this study was to examine the association between chronic mucus hypersecretion, and FEV1 decline, and subsequent hospitalization from chronic obstructive pulmonary disease (COPD). We used data from The Copenhagen City Heart Study on 5,354 women and 4,081 men 30 to 79 yr of age with assessment of smoking habits, respiratory symptoms, and spirometry at two surveys 5 yr apart. Information on COPD hospitalization during 8 to 10 yr of subsequent follow-up was obtained from a nationwide register. Chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
410
6
27

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(476 citation statements)
references
References 14 publications
(14 reference statements)
22
410
6
27
Order By: Relevance
“…Other surveys undertaken in Brazil and other countries have evaluated large samples focusing on specific diseases 15,16,17 . However, few studies have analyzed the characteristics of the surveyed individuals associated with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other surveys undertaken in Brazil and other countries have evaluated large samples focusing on specific diseases 15,16,17 . However, few studies have analyzed the characteristics of the surveyed individuals associated with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory symptoms have been associated with lower levels of pulmonary function [44][45][46][47], although patients may underestimate the morbidity associated with their disease. In a large international telephone screening of 201,921 households (in the USA, Canada, France, Italy, Germany, the Netherlands, Spain and the UK), 3,265 individuals with probable obstructive lung disease were identified.…”
Section: Respiratory Symptomsmentioning
confidence: 99%
“…For example, among individuals with the most severe breathlessness and limitation (unable to leave home secondary to dyspnoea), 35.8% described their disease as mild; of those unable to ambulate for a few minutes on level ground, 60.3% described their disease as mild [48]. Although the impairment associated with chronic cough was observed predominantly in males [44], it has been reported that females and males with chronic cough and chronic mucus hypersecretion have an accelerated decline in FEV1 [45,46] and greater mortality from COPD [47]. Whether these symptoms are markers of pathological alteration of the airways is not known.…”
Section: Respiratory Symptomsmentioning
confidence: 99%
“…Still, the chosen levels of defining rate of decline in FEV 1 may be discussed. Normal rate of decline in FEV 1 among middle-aged adults is described as 25–30 ml/year [26]. Here, we chose an even stricter criterion for groups C and D, having normal lung function at recruitment and follow-up as well as an annual decline in FEV 1 within the range of <20 ml.…”
Section: Discussionmentioning
confidence: 99%